2022
DOI: 10.3390/antiox11071408
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in the Pathogenesis of Atherothrombotic Diseases

Abstract: Oxidative stress is generated by the imbalance between reactive oxygen species (ROS) formation and antioxidant scavenger system’s activity. Increased ROS, such as superoxide anion, hydrogen peroxide, hydroxyl radical and peroxynitrite, likely contribute to the development and complications of atherosclerotic cardiovascular diseases (ASCVD). In genetically modified mouse models of atherosclerosis, the overexpression of ROS-generating enzymes and uncontrolled ROS formation appear to be associated with accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 252 publications
0
14
0
Order By: Relevance
“…Oxidative stress is generally thought to be an important contributing factor in the development and progression of atherosclerosis, raising a rational therapeutic strategy that an antioxidant therapy could protect against atherosclerotic cardiovascular diseases [ 5 ]. Unexpectedly, most, if not all, clinical trials carried out so far have consistently shown that antioxidant vitamin regimens (vitamin E or vitamin A precursor β-carotene) or selenium do not prevent cardiovascular disease events, leading to a prevailing concept that the (dietary) antioxidant therapy is unable to counteract cardiovascular diseases [ 7 , 29 , 30 , 31 , 32 ]. Of note, a number of human observational studies have shown an inverse relationship between the whole food, plant-based dietary pattern rich in antioxidant polyphenols and the incidence of cardiovascular disorders [ 8 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is generally thought to be an important contributing factor in the development and progression of atherosclerosis, raising a rational therapeutic strategy that an antioxidant therapy could protect against atherosclerotic cardiovascular diseases [ 5 ]. Unexpectedly, most, if not all, clinical trials carried out so far have consistently shown that antioxidant vitamin regimens (vitamin E or vitamin A precursor β-carotene) or selenium do not prevent cardiovascular disease events, leading to a prevailing concept that the (dietary) antioxidant therapy is unable to counteract cardiovascular diseases [ 7 , 29 , 30 , 31 , 32 ]. Of note, a number of human observational studies have shown an inverse relationship between the whole food, plant-based dietary pattern rich in antioxidant polyphenols and the incidence of cardiovascular disorders [ 8 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of ROS and oxidative stress is thought to be a critical mechanism implicated in AAA formation because these have been shown to promote inflammation, matrix degradation, and apoptosis of VSMCs in AAA formation [ 26 ]. ROS, including hydroxyl radical (•OH), superoxide (O2 − ) along with hydrogen peroxide (H2O2), are the highly reactive chemical molecules derived from oxygen [ 27 ]. Excessive ROS levels implicated in VSMCs dysfunction, DNA damage, and lipid/protein peroxidation may result in cellular injury and death irreversibly [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI) has become the most common treatment for atherosclerotic stenosis. However, complications such as inflammation, intimal hyperplasia, and in-stent restenosis remain the leading causes of the failure of PCI treatment. , Drug-eluting stents can release drugs with anticoagulant and anti-inflammatory effects at the lesion, inhibiting the development of these complications . Therefore, the advent of drug-eluting stents is seen as a revolutionary development in interventional therapy.…”
Section: Introductionmentioning
confidence: 99%